Genetic Basis of Congenital Erythrocytosis: Mutation Update and Online Databases. Issue 1 (22nd October 2013) - Bento, Celeste; Percy, Melanie J.; Gardie, Betty; Maia, Tabita Magalhães; van, Richard; Perrotta, Silverio; Della Ragione, Fulvio; Almeida, Helena; Rossi, Cedric; Girodon, François; Åström, Maria; Neumann, Drorit; et al.
<x xml:space="preserve">Abstract</x> Congenital Erythrocytosis (CE) is caused by deregulated red blood cell production where erythrocyte overproduction results in elevated hemoglobin and hematocrit levels. Despite recent important discoveries in the molecular pathogenesis of CE, the molecular causes remain to be identified in about 70% of the patients. The implementation of internet‐based erythrocytosis database and next‐generation sequencing is expected to further expand the number of genes involved in CE and to establish clinical and genotype–phenotype correlations in larger groups of individuals. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>